Sustainable marina concept with green hydrogen utilization: A case study - Karayel, G. Kubilay; Javani, Nader; Dincer, Ibrahim (ELSEVIER, 2022)
The current study investigates the green hydrogen production from renewable energy for a sustainable yacht marina. The main idea is to create a sustainable harbor for utilizing renewable energy sources using electrolysers to produce hydrogen and providing power for both marina energy demand and transportation fuel needs. Generating electricity from renewable energy resources and converting into green hydrogen in marinas are the main objectives of the current study. Solar and wave energy resources are used for calculating total hydrogen production potential. Four different sizes of luxury yachts are considered in the calculations. The considered three yacht marinas are located in Malaga, Mugla, and Istanbul. The average annual green hydrogen production potential of a marina from offshore solar energy is estimated to be 1.34, 1.38, 1.47 kt, and annual green hydrogen production from wave energy is 2.66, 3.06, 3.99 kt for the considered marinas locates in Marbella, Bodrum, and Atakoy, respectively. During the summer season, 400 small-sized, 250 medium-sized, or 100 large-sized yachts are potentially considered for fueling with green hydrogen. At maximum capacity, in Atakoy marina, which is chosen for the case study, a total of 243 hydrogen-fueled mega-yachts can potentially be refueled with green hydrogen. The study results show that the marinas selected in the specified locations appear to feasible for sustainable hydrogen applications.
Keywords: Renewable energy; Solar energy; Wave energy; Hydrogen; Sustainable marina; Energy; Exergy; Science & Technology - Other Topics; Energy & Fuels